FACTORS AFFECTING TAX AVOIDANCE IN MANUFACTURING COMPANIES LISTED IN IDX - Honorris, Prasetyo; Yuniarwati , Yuniarwati (International Journal of Application on Economics and Business, 2023)
This study aims to examine the affect of the independent variables of Sales Growth, Inventory Intensity, and Liquidity on the dependent variable, namely Tax Avoidance. The population used in this study is all manufacturing companies / taxpayers listed on the Indonesia Stock Exchange (IDX). In this study, companies/taxpayers that have met the criteria so that the data used as a sample for this study are 240 sample data of manufacturing companies/taxpayers. The researcher used the sample selection method, namely the Purposive Sampling Method, so that the researchers obtained a sample of 80 manufacturing companies / taxpayers during the 2019 – 2021 period which met the researcher's criteria. The data used by researchers is secondary data sourced from the Indonesian Stock Exchange website. The researcher tested each independent variable on the dependent variable, namely tax avoidance, and the researcher used a multiple regression model. So, the results of this study indicate that the Inventory Intensity variable has an affect on Tax Avoidance. While other independent variables, namely Sales Growth and Liquidity, obtained results that had no affect on tax avoidance.